2005
DOI: 10.1007/bf03018580
|View full text |Cite
|
Sign up to set email alerts
|

A priming technique accelerates onset of neuromuscular blockade at the laryngeal adductor muscles

Abstract: P Pu ur rp po os se e: : Priming is a known technique to accelerate onset of neuromuscular blockade (NMB). Its effect on NMB of the larynx has not been studied yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
(23 reference statements)
2
17
0
2
Order By: Relevance
“…to evaluate onset time and intubating conditions following rocuronium 0.6 mg/kg in adults patients anaesthetized with either propofol or thiopentone. The observation of Jaochim et al 7 correlated well with the present study in terms of TOF-ratio, which was around 0.57 and 0.54 at the time of successful intubation in group-II and group-III respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…to evaluate onset time and intubating conditions following rocuronium 0.6 mg/kg in adults patients anaesthetized with either propofol or thiopentone. The observation of Jaochim et al 7 correlated well with the present study in terms of TOF-ratio, which was around 0.57 and 0.54 at the time of successful intubation in group-II and group-III respectively.…”
Section: Discussionsupporting
confidence: 92%
“…They expressed their opinion that, when conducting studies of intubating conditions, only frequent-interval intubation attempts begun sufficiently early can development of optimum laryngeal conditions. This is particularly true for fast-acting muscle relaxants, such as rocuronium, where peripherally assessed onset of neuromuscular block can give no exact indication of moment when optimum laryngeal relaxation has first been achieved 7 . The use of repetitive intubation attempts to evaluate tracheal intubating conditions has been reported previously 14 .…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated a significant reduction in the onset times (74.0 vs. 44.7 s) for normal intubation doses of rocuronium (0.6 mg/kg) when primed with 0.06 mg/kg 3 min in advance. 182 When using a higher dose of rocuronium (1.0 mg/kg), another study showed equal onset times regardless of a priming dose. In the same study, patients with burn injuries also had similar onset times with or without precurarization, when the dose of rocuronium was increased to 1.5 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…A priming dose consisting of 10% of the intubation dose with a three to four minute priming interval has been considered reliable and effective. 5,11 Recently, priming doses of agents other than the non-depolarizing neuromuscular blocking agents have been used to benefit from their synergistic effects. 12,13 Rashkovsky et al suggested in their study on pancuronium and vecuronium that the formerly administered drug appeared to have a significant impact on both dose requirements and duration of action of the subsequent neuromuscular blocker.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent studies using non-depolarizing blocking agents for endotracheal intubation have reported different methods to shorten this period. 4,5 The "priming principle" is a recent commonly used approach to accelerate the effect of the basic drug by reducing the sensitivity of acetylcholine receptors by the administration of non-depolarizing blocking agents in sub-paralytic doses. This technique consists of the administration of a small dose of NMBA prior to the remaining dose.…”
mentioning
confidence: 99%